2011
DOI: 10.1007/s10534-011-9463-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic metal exposure impairs locomotion activity in Drosophila melanogaster: a model to study Parkinsonism

Abstract: The biometals iron (Fe), manganese (Mn) and copper (Cu) have been associated to Parkinson's disease (PD) and Parkinsonism. In this work, we report for the first time that acute (15 mM for up to 5 days) or chronic (0.5 mM for up to 15 days) Fe, Mn and Cu exposure significantly reduced life span and locomotor activity (i.e. climbing capabilities) in Drosophila melanogaster. It is shown that the concentration of those biometals dramatically increase in Drosophila's brain acutely or chronically fed with metal. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 68 publications
7
40
1
Order By: Relevance
“…However, our findings are also in contrast to previous studies in mammals [18] and Drosophila [21], which indicated that Mn 2þ exposure leads to dopaminergic neuronal loss, and overall reduced levels of dopamine in the brain. We do not yet understand the main reason for the differences between our current findings and previous reports.…”
Section: Resultscontrasting
confidence: 99%
“…However, our findings are also in contrast to previous studies in mammals [18] and Drosophila [21], which indicated that Mn 2þ exposure leads to dopaminergic neuronal loss, and overall reduced levels of dopamine in the brain. We do not yet understand the main reason for the differences between our current findings and previous reports.…”
Section: Resultscontrasting
confidence: 99%
“…climbing capabilities) in D. melanogaster. Bonilla-Ramirez, Jimenez-Del-Rio, and Velez-Pardo (2011) found that the concentrations of those metals markedly rose in D. melamogaster brain in acute or chronically fed flies associated with neurodegeneration of several dopaminergic neuronal clusters. Data suggest that Fe, Mn, and Cu are capable of destroying dopaminergic neurons in fly brain, thereby impairing their movement capabilities.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, our findings of a decreased locomotor activity in Mn-fed flies (Mn and Mn þ resveratrol groups) might involve the dysfunction of other types of neurons. However, Bonilla-Ramirez, Jimenez-Del-Rio, and Velez-Pardo (2011) reported that acute (15 mM for up to 5 days) or chronic (0.5 mM for up to 15 days) Fe, Mn, and Cu exposure significantly reduced the life span and motor activity (i.e. climbing capabilities) in D. melanogaster.…”
Section: Discussionmentioning
confidence: 97%
“…There are about 200 DAergic neurons in the flies; however, they are responsible for modulating a wide range of behaviors ranging from sleep and locomotion to courtship and learning (Van Swinderen and Andretic 2011). Under chronic Mn exposure, flies show reduced survival, life-span, and reduced locomotor activity, with Mn showing greater toxic effects than iron and copper (Bonilla-Ramirez et al 2011). Mn accumulates in the head of the flies, and the number of DAergic neuronal clusters labeled with green fluorescent protein (GFP) is reduced upon Mn treatment (Bonilla-Ramirez et al 2011).…”
Section: Studies In Drosophila Melanogastermentioning
confidence: 99%
“…Under chronic Mn exposure, flies show reduced survival, life-span, and reduced locomotor activity, with Mn showing greater toxic effects than iron and copper (Bonilla-Ramirez et al 2011). Mn accumulates in the head of the flies, and the number of DAergic neuronal clusters labeled with green fluorescent protein (GFP) is reduced upon Mn treatment (Bonilla-Ramirez et al 2011). This study also showed that Mn-induced DAergic degeneration was associated with impairment in the climbing behavior and mobility shortage analogous to fly PD models.…”
Section: Studies In Drosophila Melanogastermentioning
confidence: 99%